The Tail of the Late Jurassic Sauropod Giraffatitan brancai: Digital Reconstruction of Its Epaxial and Hypaxial Musculature, and Implications for Tail Biomechanics - Díez Díaz, Verónica; Demuth, Oliver E.; Schwarz, Daniela; Mallison, Heinrich (Frontiers in Earth Science, 2020)
Dinosaur locomotion and biomechanics, especially of their pelvic girdles and hind limbs, have been analysed in numerous studies. However, detailed volumetric musculoskeletal models of their tails are rarely developed. Here, we present the first detailed three-dimensional volumetric reconstruction of the caudal epaxial and hypaxial musculature of the Late Jurassic sauropod Giraffatitan brancai, and highlight the importance and necessity of 3D modelling in musculoskeletal reconstructions. The tail of this basal macronarian is relatively short compared to diplodocids and other coexisting macronarians. The centre of mass lies well in front of the hind limbs, which support only ca. half the body weight. Still, our reconstruction suggests a total weight for the entire tail of ca. 2500 kg. We conclude that the hypaxial and hind limb muscles (more specifically the M. caudofemoralis longus and its counterpart the M. ilioischiocaudalis) in Giraffatitan were well developed and robustly built, compensating for the shorter length of the M. caufodemoralis longus, the main hind limb retractor muscle, in comparison with other sauropods. Our methodology allows a better-constrained reconstruction of muscle volumes and masses, in extinct taxa, and thus force and weight distributions, throughout the tail, than non-volumetric approaches.